Der steinige Weg vom Wissen zum Können: Zum schwierigen Verhältnis von Theorie und Praxis bei der Betreuung zukünftiger Geschichtslehrkräfte in Langzeitpraktika - Hartung, Olaf; Krebs, Alexandra; Fastlabend-Vargas, Daniel; Meyer-Hamme, Johannes (Theorie und Praxis in der Lehrerbildung.Verhältnisbestimmungen aus der Perspektive von Fachdidaktiken)

„Da öffnet er ihnen das Verständnis, sodass sie die Schriften verstanden“ (Lk 24,45) - Breuer, Saskia Rebecca (Der Dom. Katholisches Magazin im Erzbistum Paderborn)

The Rise of Interactional Multimodality in Human-Computer Interaction - Klowait, Nils; Ерофеева, Мария Александровна (The monitoring of public opinion economic&social changes)
The field of human-computer interaction (HCI) investigates the intersection between the design of devices and users. From an early focus on interaction modeling based on psychological experiments, the field has since experienced a shift towards the study of how actual humans interact with autonomous devices. The field became conductive to ethnographic, observational and videographic studies of human-device interaction. Conversation-analytic HCI became possible. That said, this new wave of researchers was never truly able to dethrone the psychological common sense of the field. With recent developments in both the technical-sensorial capabilities and outward actuational range of embodied virtual agents, the field of HCI has once again returned to the question of the sequential unfolding of the interaction between users and intelligent agents, and the multimodal interactional repertoire that is deployed throughout. This review will highlight the situational orientation of high-impact research in the field, and relate it to the cotemporaneous development of ethnomethodological and conversation analytic frameworks. Acknowledgments. The article was prepared in the framework of a research grant funded by the Ministry of Science and Higher Education of the Russian Federation (grant ID: 075-15-2020-908). The article was prepared in cooperation with the Sber (ex. – Sberbank’s) Gamification Lab.
Keywords: Economics; Econometrics and Finance (miscellaneous); Sociology and Political Science

Home-Office. Kulturelle Formationen häuslicher Arbeit - Miggelbrink, Monique; Bartz, Christina (Selbstbehältnisse. Orte und Gegenstände der Aufbewahrung von Subjektivität)

Forschungsfelder für Künstliche Intelligenz in der strategischen Produktplanung - Ködding, Patrick; Dumitrescu, Roman (Digitalisisierung souverän gestalten)

Selective area growth of cubic gallium nitride on silicon (001) and 3C-silicon carbide (001) - Meier, F.; Protte, M.; Baron, E.; Feneberg, M.; Goldhahn, R.; Reuter, Dirk; As, Donat Josef (AIP Advances)

“Seeing Is Believing”—In-Depth Analysis by Co-Imaging of Periodically-Poled X-Cut Lithium Niobate Thin Films - Reitzig, Sven; Rüsing, Michael; Zhao, Jie; Kirbus, Benjamin; Mookherjea, Shayan; Eng, Lukas M. (Crystals)
Nonlinear and quantum optical devices based on periodically-poled thin film lithium niobate (PP-TFLN) have gained considerable interest lately, due to their significantly improved performance as compared to their bulk counterparts. Nevertheless, performance parameters such as conversion efficiency, minimum pump power, and spectral bandwidth strongly depend on the quality of the domain structure in these PP-TFLN samples, e.g., their homogeneity and duty cycle, as well as on the overlap and penetration depth of domains with the waveguide mode. Hence, in order to propose improved fabrication protocols, a profound quality control of domain structures is needed that allows quantifying and thoroughly analyzing these parameters. In this paper, we propose to combine a set of nanometer-to-micrometer-scale imaging techniques, i.e., piezoresponse force microscopy (PFM), second-harmonic generation (SHG), and Raman spectroscopy (RS), to access the relevant and crucial sample properties through cross-correlating these methods. Based on our findings, we designate SHG to be the best-suited standard imaging technique for this purpose, in particular when investigating the domain poling process in x-cut TFLNs. While PFM is excellently recommended for near-surface high-resolution imaging, RS provides thorough insights into stress and/or defect distributions, as associated with these domain structures. In this context, our work here indicates unexpectedly large signs for internal fields occurring in x-cut PP-TFLNs that are substantially larger as compared to previous observations in bulk LN.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Photoconduction of Polar and Nonpolar Cuts of Undoped Sr0.61Ba0.39Nb2O6 Single Crystals - Beyreuther, Elke; Ratzenberger, Julius; Roeper, Matthias; Kirbus, Benjamin; Rüsing, Michael; Ivleva, Liudmila I.; Eng, Lukas M. (Crystals)
In the last two decades, variably doped strontium barium niobate (SBN) has attracted a lot of scientific interest mainly due to its specific non-linear optical response. Comparably, the parental compound, i.e., undoped SBN, appears to be less studied so far. Here, two different cuts of single-crystalline nominally pure strontium barium niobate in the composition Sr0.61Ba0.39Nb2O6 (SBN61) are comprehensively studied and analyzed with regard to their photoconductive responses. We present conductance measurements under systematically varied illumination conditions along either the polar z-axis or perpendicular to it (x-cut). Apart from a pronounced photoconductance (PC) already under daylight and a large effect upon super-bandgap illumination in general, we observe (i) distinct spectral features when sweeping the excitation wavelength over the sub-bandgap region as then discussed in the context of deep and shallow trap states, (ii) extremely slow long-term relaxation for both light-on and light-off transients in the range of hours and days, (iii) a critical dependence of the photoresponse on the pre-illumination history of the sample, and (iv) a current–voltage hysteresis depending on both the illumination and the electrical-measurement conditions in a complex manner.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Tricyanidoferrates(−IV) and Ruthenates(−IV) with Non‐Innocent Cyanido Ligands - Jach, Franziska; Wagner, Frank R.; Amber, Zeeshan H.; Rüsing, Michael; Hunger, Jens; Prots, Yurii; Kaiser, Martin; Bobnar, Matej; Jesche, Anton; Eng, Lukas M.; Ruck, Michael; Höhn, Peter (Angewandte Chemie International Edition)
Exceptionally electron-rich, nearly trigonal-planar tricyanidometalate anions [Fe(CN)3]7− and [Ru(CN)3]7− were stabilized in LiSr3[Fe(CN)3] and AE3.5[M(CN)3] (AE=Sr, Ba; M=Fe, Ru). They are the first examples of group 8 elements with the oxidation state of −IV. Microcrystalline powders were obtained by a solid-state route, single crystals from alkali metal flux. While LiSr3[Fe(CN)3] crystallizes in P63/m, the polar space group P63 with three-fold cell volume for AE3.5[M(CN)3] is confirmed by second harmonic generation. X-ray diffraction, IR and Raman spectroscopy reveal longer C−N distances (124–128 pm) and much lower stretching frequencies (1484–1634 cm−1) than in classical cyanidometalates. Weak C−N bonds in combination with strong M−C π-bonding is a scheme also known for carbonylmetalates. Instead of the formal notation [Fe−IV(CN−)3]7−, quantum chemical calculations reveal non-innocent intermediate-valent CN1.67− ligands and a closed-shell d10 configuration for Fe, that is, Fe2−.
Keywords: General Chemistry; Catalysis

Quantifying the coherent interaction length of second-harmonic microscopy in lithium niobate confined nanostructures - Amber, Zeeshan H.; Kirbus, Benjamin; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Thin-film lithium niobate (TFLN) in the form of x- or z-cut lithium-niobate-on-insulator has attracted considerable interest as a very promising and novel platform for developing integrated optoelectronic (nano)devices and exploring fundamental research. Here, we investigate the coherent interaction length lc of optical second-harmonic generation (SHG) microscopy in such samples, that are purposely prepared into a wedge shape, in order to elegantly tune the geometrical confinement from bulk thicknesses down to approximately 50 nm. SHG microscopy is a very powerful and non-invasive tool for the investigation of structural properties in the biological and solid-state sciences, especially for visualizing and analyzing ferroelectric domains and domain walls. However, unlike in bulk lithium niobate (LN), SHG microscopy in TFLN is impacted by interfacial reflections and resonant enhancement, both of which rely on film thickness and substrate material. In this paper, we show that the dominant SHG contribution measured on TFLN in backreflection is the co-propagating phase-matched SHG signal and not the counter-propagating SHG portion as is the case for bulk LN samples. Moreover, lc depends on the incident pump laser wavelength (sample dispersion) but also on the numerical aperture of the focussing objective in use. These experimental findings on x- and z-cut TFLN are excellently backed up by our advanced numerical simulations.
Keywords: General Physics and Astronomy

Potassium Ion Conductivity in the Cubic Labyrinth of a Piezoelectric, Antiferromagnetic Oxoferrate(III) Tellurate(VI) - Albrecht, Ralf; Hoelzel, Markus; Beccard, Henrik; Rüsing, Michael; Eng, Lukas; Doert, Thomas; Ruck, Michael (Chemistry – A European Journal)
Orange-colored crystals of the oxoferrate tellurate K12+6xFe6Te4−xO27 [x=0.222(4)] were synthesized in a potassium hydroxide hydroflux with a molar water–base ratio n(H2O)/n(KOH) of 1.5 starting from Fe(NO3)3 ⋅ 9H2O, TeO2 and H2O2 at about 200 °C. By using (NH4)2TeO4 instead of TeO2, a fine powder consisting of microcrystalline spheres of K12+6xFe6Te4−xO27 was obtained. K12+6xFe6Te4−xO27 crystallizes in the acentric cubic space group Iurn:x-wiley:09476539:media:chem202102464:chem202102464-math-0001 3d. [FeIIIO5] pyramids share their apical atoms in [Fe2O9] groups and two of their edges with [TeVIO6] octahedra to form an open framework that consists of two loosely connected, but not interpenetrating, chiral networks. The flexibility of the hinged oxometalate network manifests in a piezoelectric response similar to that of LiNbO3.The potassium cations are mobile in channels that run along the <111> directions and cross in cavities acting as nodes. The ion conductivity of cold-pressed pellets of ball-milled K12+6xFe6Te4−xO27 is 2.3×10^(−4) S ⋅ cm^(−1) at room temperature. Magnetization measurements and neutron diffraction indicate antiferromagnetic coupling in the [Fe2O9] groups.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Quantifying the refractive index of ferroelectric domain walls in periodically poled LiNbO3 single crystals by polarization-sensitive optical coherence tomography - Golde, Jonas; Rüsing, Michael; Rix, Jan; Eng, Lukas M.; Koch, Edmund (Optics Express)
Domain walls (DWs) in ferroelectric (FE) and multiferroic materials possess an ever-growing potential as integrated functional elements, for instance in optoelectronic nanodevices. Mandatory, however, is the profound knowledge of the local-scale electronic and optical properties, especially at DWs that are still incompletely characterized to date. Here, we quantify the refractive index of individual FE DWs in periodically-poled LiNbO 3 (PPLN) single crystals. When applying polarization-sensitive optical coherence tomography (PS-OCT) at 1300 nm using circular light polarization, we are able to probe the relevant electro-optical properties close to and at the DWs, including also their ordinary and extraordinary contributions. When comparing to numerical calculations, we conclude that the DW signals recorded for ordinary and extraordinary polarization stem from an increased refractive index of at least Δn > 2·10 −3 that originates from a tiny region of < 30 nm in width. PS-OCT hence provides an extremely valuable tool to decipher and quantify subtle changes of refractive index profiles for both inorganic and biomedical nanomaterial systems.
Keywords: Atomic and Molecular Physics; and Optics

Broadband coherent anti-Stokes Raman scattering for crystalline materials - Hempel, Franz; Reitzig, Sven; Rüsing, Michael; Eng, Lukas M. (Physical Review B)
Broadband coherent anti-Stokes Raman scattering (B-CARS) has emerged in recent years as a promising chemosensitive high-speed imaging technique. B-CARS allows for the detection of vibrational sample properties in analogy to spontaneous Raman spectroscopy, but also makes electronic sample environments accessible due to its resonant excitation mechanism. Nevertheless, this technique has only gained interest in the biomedical field so far, whereas CARS investigations on solid-state materials are rare and concentrate on layered, two-dimensional materials such as graphene and hexagonal boron nitride . In this work, we discuss the specific properties of this technique when applied to single-crystalline samples, with respect to signal generation, phase matching, and selection rules in the model systems lithium niobate and lithium tantalate. Via polarized B-CARS measurements and subsequent phase retrieval, we validate the predicted selection rules, unequivocally assign the phonons of the A1(TO), E(TO) and A1(LO) branches to the detected CARS peaks, and address differences in spontaneous Raman spectroscopy concerning peak frequencies and scattering efficiencies. We thus establish this technique for future investigations of solid-state materials, specifically in the field of ferroelectric single crystals.

Mental body rotation with egocentric and object-based transformations in different postures: standing vs. balancing - Budde, Kirsten; Jöllenbeck, Thomas; Barela, José A.; Figueiredo, Gabriella A.; Weigelt, Matthias (Brazilian Journal of Motor Behavior)
BACKGROUND: Previous studies suggest better visual-spatial processing when participants are tested in postures in which dynamic stability is challenged. The question arises if this is also true for the performance in mental body-rotation tasks (MBRT). AIM: Taking the embodied cognition approach into account, the first aim of the present study was to examine the potential influence of different demands on dynamic stability for two postures (parallel stand vs. tandem stand) on solving two versions of the MBRT, inducing either an object-based or an egocentric perspective transformation strategy. The second aim was to investigate if these different demands on dynamic stability are reflected in postural sway parameters. METHOD: Thirty participants (18 females and 12 males) were tested in the two MBRTs and in a control condition. All tasks were performed while standing on a balance beam in tandem stand and in a feet parallel position on a force plate. RESULTS: The results for response time and response error revealed effects of rotation angle and task, but no effect of posture. The analyzed Center of Pressure (CoP) data revealed a reduction of body sway during the MBRT for egocentric perspective transformations. CONCLUSION: The results indicate that participants performed better for egocentric than for object-based transformations and that the egocentric transformation leads to more postural stability than the object-based.

Mental body rotation with egocentric and object-based transformations in different postures: sitting vs. standing. - Budde, Kirsten; Barela, José A; Figueiredo, Gabriella A; Weigelt, Matthias (TeaP 2021 - Abstracts of the 63rd Conference of Experimental Psychologists.)

Mechanical joining of glass fibre reinforced polymer (GFRP) through an innovative solid self-piercing rivet - Han, Daxin; Yang, Keke; Meschut, Gerson (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

A first introduction to data science education in secondary schools: Teaching and learning about data exploration with CODAP using survey data - Frischemeier, Daniel; Biehler, Rolf; Podworny, Susanne; Budde, Lea (Teaching Statistics)
Abstract In this paper, we will describe an introduction to Data Science for secondary school students. We will report on the design and implementation of an introductory unit on “Data and data detectives with CODAP” in which secondary school students used the online tool CODAP to explore real and meaningful survey data on leisure time activities and media use (so‐called JIM‐PB data) in a statistical project setting as a starting point for data science. The JIM‐PB data set served as a valuable data set that offered meaningful and exciting opportunities for data exploration for secondary school students, and CODAP proved to be a valuable tool for the first explorations of this data.
Keywords: Education; Statistics and Probability

Integration fachwissenschaftlicher und fachdidaktischer Komponenten in der Lehramtsausbildung Mathematik Grundschule am Beispiel einer Veranstaltung zur Leitidee „Daten, Häufigkeit und Wahrscheinlichkeit“ - Frischemeier, Daniel; Podworny, Susanne; Biehler, Rolf (Konzepte und Studien zur Hochschuldidaktik und Lehrerbildung Mathematik)

Zur neuen Bedeutung von Daten in Data Science und künstlicher Intelligenz - Höper, Lukas; Podworny, Susanne; Hüsing, Sven; Schulte, Carsten; Fleischer, Yannik; Biehler, Rolf; Frischemeier, Daniel; Malatyali, Hülya

When differential privacy meets NLP: The devil is in the detail - Habernal, Ivan (Proceedings of the 2021 Conference on Empirical Methods in Natural Language Processing)

Alternating Asymmetrical Phase-Shift Modulation for Full-Bridge Converters with Balanced Switching Losses to Reduce Thermal Imbalances - Rehlaender, Philipp; Unruh, Roland; Schafmeister, Frank; Böcker, Joachim (2021 IEEE Applied Power Electronics Conference and Exposition (APEC))
Phase-shift modulated full bridge converters suffer from thermal imbalances of the inverter switches. The lagging leg switches are subject to larger commutation currents compared to those of the leading leg as the transformer current reduces in the freewheeling interval. Furthermore, after this interval, the energy in the series inductance may not be large enough to achieve zero-voltage switching (ZVS) for the leading leg. Both effects result in thermal imbalances. This paper analyzes the alternating-asymmetrical phase-shift modulation to achieve balanced conduction and switching losses for all four switches while showing that this modulation is easily implemented on standard DSPs. The modulation has been implemented to LLC converters where experimental measurement results proved its effectiveness for LLC converters by reducing the temperature deviation from 6.3 K to only 0.2 K such that the peak temperature is reduced from 95 °C to 92 °C. The paper also proves that the modulation can be utilized to improve the efficiency of LLC converters operated at very low gains while simultaneously reducing the junction temperature of all four switches compared to the conventional complementary modulation. Finally, EMI implications are analyzed, which show that the modulation may be beneficial for reducing the common-mode emissions around the operating frequency.
Keywords: Phase-Shifted Full Bridge; Full-Bridge Converter; Phase-Shift Control; Phase-Shift Modulation; LLC Converter; Thermal Balancing

Geometrisches Begriffsverständnis in der Grundschule am Beispiel der Begriffe Viereck, Rechteck und Quadrat - Bruns, Julia; Unterhauser, Elisabeth; Gasteiger, Hedwig (Journal für Mathematik-Didaktik)
Zusammenfassung Zu den ersten geometrischen Begriffen, die Kinder bereits im Elementar- und Primarbereich lernen, zählen u. a. Viereck, Rechteck und Quadrat. Studien zeigen, dass Lernende bereits früh individuelle Vorstellungen, sog. individuelle Begriffskonzepte, zu diesen Begriffen aufbauen. Zwar wird die Entwicklung von Begriffsverständnis in verschiedenen mathematikdidaktischen Stufenmodellen dargestellt, diese sind jedoch generisch und beschreiben nicht explizit die Entwicklung der ersten individuellen Begriffskonzepte von Lernenden zu Viereck, Rechteck und Quadrat. Aus empirischer Sicht liegen verschiedene Studien vor, die einzelne Aspekte der individuellen Begriffskonzepte von Lernenden unterschiedlicher Altersgruppen zu diesen Begriffen ausleuchten. Um Begriffsbildungsprozesse aus empirischer Sicht detaillierter entlang der jeweils vorherrschenden individuellen Begriffskonzepte zu beschreiben, fehlen insbesondere Studien in der Grundschule, die alle vier Klassenstufen betrachten und dabei differenzierte Erkenntnisse zu verschiedenen theoretischen Indikatoren des Begriffsverständnisses liefern. Daher geht die vorliegende Studie der Frage nach, welches Verständnis der Begriffe Viereck, Rechteck und Quadrat Schülerinnen und Schüler der Jahrgangsstufen 1, 2, 3 und 4 zeigen. Dazu wurde eine Quasi-Längsschnittstudie mit N = 456 Grundschulkindern (ca. 100 pro Jahrgangsstufe) durchgeführt. Die Ergebnisse geben detaillierte Einblicke in die individuellen Begriffskonzepte der Lernenden und zeigen, dass Lernende zunehmend Eigenschaften der Figuren berücksichtigen, jedoch individuelle Begriffskonzepte über lange Zeit auch prototypisch geprägt sind. Implikationen dieser Ergebnisse für Forschung und Praxis werden diskutiert.
Keywords: Education; General Mathematics

Tocotronic - Hoffnung (2020). - Jacke, Christoph (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr.)

Teilhabe von Eltern an schulischem Lernen mit Family-Literacy-Programmen. Langzeiteffekte von „LIFE – Lesen in Familie erleben“ auf die elterliche Unterstützung beim Lesenlernen - Bonanati, Sabrina; Gruchel, Nicole; Kurock, Ricarda; Buhl, Heike M. (Die Deutsche Schule)
Family-Literacy-Programme stellen eine gute Möglichkeit dar, Eltern in Bildungsprozesse einzubeziehen. Am Beispiel des Programms „LIFE – Lesen in Familie erleben“ wird die Wirkung auf elterliche Unterstützung beim Lesenlernen von Erstklässler*innen unter Einbezug von Eltern- und Kinderperspektive untersucht. Sowohl direkt nach dem Programm als auch ein halbes Jahr später wirkte das Programm positiv auf verschiedene Arten der Anschlusskommunikation beim gemeinsamen Lesen.
Keywords: Kooperation; Familie; Lesekompetenz; Längsschnittstudie; Intervention

Schule und außerschulische Bildungspartner an der Schnittstelle von formalen und non-formalen Bildungsprozessen - Empirische Befunde zur Kooperation und professionellen Handlungskompetenz - Limpinsel, Inga; Engemann, Mario; Neuberger, Olga; Serova, Katja; Aßmann, Sandra (Kooperation - Koordination - Kollegialität. Befunde und Diskurse zum (multi-)professionellen Zusammenwirken pädagogischer Akteur*innen an Schulen)

Lehrerkooperation und Digitalisierung - Gestaltung digital-kooperativer Arbeitsbeziehungen von Lehrkräften und ReferendarInnen am Beispiel des Schulfachs Pädagogik - Engemann, Mario; Herzig, Bardo (Fachliche Bildung und digitale Transformation - Fachdidaktische Forschung und Diskurse. Fachtagung der Gesellschaft für Fachdidaktik 2020)

Lehrerkooperation vor dem Hintergrund der Digitalisierung: Eine Untersuchung innerhalb von Fachkollegien im gymnasialen Schulfach Pädagogik - Engemann, Mario; Herzig, Bardo

When agency “fits” regardless of gender: Perceptions of applicant fit when job and organization signal male stereotypes - Dutz, Regina; Hubner-Benz, Sylvia; Peus, Claudia (Personnel Psychology)
Evaluators’ fit assessments are not only influenced by applicants’ qualities, but also by stereotypes, especially in recruitment for high‐status jobs in male‐dominated fields. The unidimensional agentic stereotype of these work contexts signals agentic job and organizational requirements (stereotypically male qualities such as achievement orientation), although the actual requirements usually also include communality (stereotypically female qualities such as interpersonal skills). In five experiments, we investigate the relevance of perceived applicant agency for perceived applicant fit, the influence of recruitment material, contextual differences, and the role of applicant gender. Our findings indicate that perceived applicant agency drives perceived person‐job and person‐organization fit in strictly male stereotyped work contexts, regardless of gender, and agentic recruitment material enhances this effect. Contrasting different contexts (high‐ with low‐status jobs and a male‐dominated with a gender‐balanced and female‐dominated field) revealed that the relevance of perceived agency increases with perceived job status, and the relevance of perceived communality decreases with the expected share of men. Although women were perceived as highly agentic in strictly male stereotyped work contexts, their need to be perceived as agentic also was higher than for men, due to the perceived lack of fit between women and high‐status jobs.
Keywords: Organizational Behavior and Human Resource Management; Applied Psychology

Narratives in entrepreneurial ecosystems: drivers of effectuation versus causation - Hubner-Benz, Sylvia; Most, Fabian; Wirtz, Jochen; Auer, Christine (Small Business Economics)
This paper introduces narratives in entrepreneurial ecosystems as drivers of effectuation vs. causation. Drawing on 43 interviews with successful players in Silicon Valley, Munich, and Singapore, we found ecosystem-specific narratives indicate what is common, appropriate, and successful in each ecosystem, and these narratives encourage either effectuation or causation. Our findings indicate that the narratives in the ecosystem in Silicon Valley facilitate effectuation, in Munich causation, and in Singapore a cautious balance of both. Our research suggests that narratives can explain mechanisms how ecosystems influence entrepreneurship: the national culture, market characteristics, available resources, and networks in an ecosystem spark ecosystem-specific narratives, which in turn shape tendencies towards effectuation and causation. Thereby, we introduce a new ecosystem-focused perspective on predictors of effectuation and causation.
Keywords: Economics and Econometrics; General Business; Management and Accounting

Weder - Noch. Was mich theologisch prägt - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik. (https://www.theomag.de/129/hsw22.pdf))

Fehlerbearbeitung bei mathematischen Textaufgaben – Sprachliche und strategische Fehlerursachen und ihre Bearbeitung - Prediger, Susanne; Dröse, Jennifer (Lernen und Lernstörungen, 10(2))

System mit optischer Trägerverteilung - Kruse, Stephan; Scheytt, J. Christoph

Elektrooptischer Regelkreis - Kruse, Stephan; Scheytt, J. Christoph

Fälle als Reflexionsanlass im Unterricht: Theoretische und empirische Zugänge zur Fallarbeit als Methode im Schulfach Erziehungswissenschaft - Engemann, Mario; Gather, Katharina; Martin, Alexander

Neurophysiology of embodied mental rotation: Event‐related potentials in a mental rotation task with human bodies as compared to alphanumeric stimuli - Krause, Daniel; Richert, Benjamin; Weigelt, Matthias (European Journal of Neuroscience)
Abstract The present study examines if the neural signature of information processing in mental rotation tasks is moderated by stimulus characteristics (e.g., body‐related vs. non‐body‐related stimuli). In the present experiment, stimulus sets of human figures (back view; left vs. right arm abduction) and alphanumeric characters (‘R’; normal vs. mirrored view) were scrutinized with event‐related potentials (ERPs) in the electroencephalography (EEG). Participants had to judge parity between an upright (0° orientation) and a comparison stimulus (stimulus disparity; 0°, 45°, 90°, 135° or 180°). There was a main effect of stimulus disparity for the behavioural (response time and error rates), as well as for the neural data (rotation‐related negativity, RRN). The interaction of stimulus disparity and stimulus type was significant for the RRN, but not for the response time. Lower RRN amplitudes for letters indicate a more pronounced use of alternative processes (e.g., memory retrieval), which seems to be reflected in higher N350 amplitudes. Moreover, the increase of the RRN amplitude and the increase in response time as a function of disparity were positively correlated. Task differences were evident for several ERP components (i.e., N150, P150 and N250), being independent of disparity, which might reflect differences in early and late object cognition prior to the mental rotation process itself. This might be associated with the task‐dependent activation of embodied cognition processes in mental rotation tasks.
Keywords: General Neuroscience

Valence-dependent neural correlates of augmented feedback processing in extensive motor sequence learning – Part II: Predictive value of event-related potentials for behavioral adaptation and learning - Margraf, Linda; Krause, Daniel; Weigelt, Matthias (Neuroscience)
Keywords: General Neuroscience

Stimulating performance: A scoping review on transcranial electrical stimulation effects on olympic sports - Friehs, Maximilian A.; Whelan, Eric; Güldenpenning, Iris; Krause, Daniel; Weigelt, Matthias (Psychology of Sport and Exercise)
Keywords: Applied Psychology

Valence-dependent Neural Correlates of Augmented Feedback Processing in Extensive Motor Sequence Learning – Part I: Practice-related Changes of Feedback Processing - Margraf, Linda; Krause, Daniel; Weigelt, Matthias (Neuroscience)
Keywords: General Neuroscience

Die Förderung demokratischer Grundhaltungen als Teil professioneller Kompetenz angehender Lehrpersonen: Darstellung eines Forschungsvorhabens - Wehde, Janis; Bloh, Bea

Salutogenes Leitungshandeln. Ein Ansatz zur Gesundheitsförderung und Qualitätsentwicklung in der Schule. - Bloh, Bea; Wehde, Janis (Lernende Schule)

Präkonzepte von Grundschulkindern zur Zeitzeug*innenbefragung – Eine empirische Untersuchung zu Kompetenzen historischen Denkens - Diederich, Julia
Die Zeitzeug*innenbefragung gilt als kindgemäßer Zugang zur Alltags- und Zeitgeschichte. Sie charakterisiert sich sowohl als geschichtswissenschaftliche Forschungsmethode als auch Unterrichtsmethode zur Erstellung, Bearbeitung und Interpretation historischer Quellen mittels Erinnerungsinterviews zu vergangenen Erlebnissen und Erfahrungen (vgl. Michalik 2017, Schreiber 2009). Trotz einer bildungspolitischen Empfehlung der Methode der Zeitzeug*innenbefragung ab dem Anfangsunterricht des Sachunterrichts (vgl. u.a. Niedersächsisches Kultusministerium 2017), standen bislang im (inter-)nationalen Raum Studien, die die Zeitzeug*innenbefragung als didaktisches Arrangement historischen Lernens im Sachunterricht untersuchen sowie die Kinderperspektive auf die Methode der Zeitzeug*innenbefragung erfassen, aus. Entsprechend fokussiert die vorliegende, explorative und qualitativ angelegte Studie die Präkonzepte von Grundschulkindern zur Methode der Zeitzeug*innenbefragung. Mittels leitfadengestützter teilstandardisierter Einzelinterviews wurden die Präkonzepte zur Methode sowie zum Wissenschaftsverständnis bezüglich Zeitzeug*innen als historische Quelle rekonstruiert (vgl. Fuhs 2012, Helfferich 2011). Das Sample setzte sich aus Grundschulkindern der zweiten und vierten Klasse zusammen. Zur Bearbeitung und Auswertung des Datenmaterials diente eine in Anlehnung an die Lehr- und Lernforschung adaptierte Vorgehensweise der Qualitativen Inhaltsanalyse, die entsprechend modifiziert und erweitert wurde (vgl. Kuckartz 2018). Die Befunde der Studie zeigen differenzierte Präkonzepte der interviewten Zweit- und Viertklässler*innen zum Kontext der Methode der Zeitzeug*innenbefragung auf. Im Weiteren verweisen die Befunde darauf, dass die Zeitzeug*innenbefragung als Unterrichtsmethode ihre Legitimation im historischen Lernen mit Beginn des Anfangsunterrichts in der Grundschule hat.
Keywords: Präkonzepte; Zeitzeugenbefragung; Historisches Lernen; Sachunterricht; qualitative Forschung

Die Zeitzeugenbefragung aus der Sicht von Grundschulkindern - Diederich, Julia (Historisches Lernen in der Primarstufe. Standpunkte – Herausforderungen – Perspektiven)

Simmels Abhandlungen zu Kant - Luft, Sebastian (Simmel-Handbuch)

Cassirer’s Children, Special Topics Issue
Keywords: General Medicine

Wilhelm Windelband. Präludien

Graph-PIT: Generalized Permutation Invariant Training for Continuous Separation of Arbitrary Numbers of Speakers - von Neumann, Thilo; Kinoshita, Keisuke; Boeddeker, Christoph; Delcroix, Marc; Haeb-Umbach, Reinhold (Interspeech 2021)
Automatic transcription of meetings requires handling of overlapped speech, which calls for continuous speech separation (CSS) systems. The uPIT criterion was proposed for utterance-level separation with neural networks and introduces the constraint that the total number of speakers must not exceed the number of output channels. When processing meeting-like data in a segment-wise manner, i.e., by separating overlapping segments independently and stitching adjacent segments to continuous output streams, this constraint has to be fulfilled for any segment. In this contribution, we show that this constraint can be significantly relaxed. We propose a novel graph-based PIT criterion, which casts the assignment of utterances to output channels in a graph coloring problem. It only requires that the number of concurrently active speakers must not exceed the number of output channels. As a consequence, the system can process an arbitrary number of speakers and arbitrarily long segments and thus can handle more diverse scenarios. Further, the stitching algorithm for obtaining a consistent output order in neighboring segments is of less importance and can even be eliminated completely, not the least reducing the computational effort. Experiments on meeting-style WSJ data show improvements in recognition performance over using the uPIT criterion.
Keywords: Continuous speech separation; automatic speech recognition; overlapped speech; permutation invariant training

Speeding Up Permutation Invariant Training for Source Separation - von Neumann, Thilo; Boeddeker, Christoph; Kinoshita, Keisuke; Delcroix, Marc; Haeb-Umbach, Reinhold (Speech Communication; 14th ITG Conference)

Handling of explicit Uncertainty in Requirements Change Management - Gräßler, Iris; Pottebaum, Jens; Oleff, Christian; Preuß, Daniel (Proceedings of the Design Society)
Abstract Innovation projects are characterized by numerous uncertainties. Typical concepts in development management like the application of safety coefficients imply limitations of the solution space. In contrast, explicit handling of uncertainties can support engineers in understanding the problem space and in utilising the full potential of the design space along iterative product development steps. As a result from literature analysis, there is a lack of a support for product development that addresses the specific problem of uncertainty and risk in the context of requirement changes. The aim of the contribution at hand is to enhance the efficient development of complex interdisciplinary systems by enabling uncertainty handling in requirements change management. Based on a classification of uncertainty types resulting in a descriptive model, risk management measures are identified to support requirements engineers. The proposed method includes identification & modelling, analysis, treatment and monitoring of risks and counter-measures. By applying this method, engineers are supported in adopting agile approaches and enabling flexible Requirements Engineering.

Ein reaktiver Modellierungsansatz für Mensch-Roboter-Kollaboration in Rettungs- und Brandszenarien der Feuerwehr - Gürtler, Marius; Mandischer, Nils; Hüsing, Mathias; Corves, Burkhard; Pottebaum, Jens; Roesmann, Daniel; Gräßler, Iris (7. IFToMM D-A-CH Konferenz 2021; 18. - 19. Feb. 2021 IFToMM D-A-CH)

Fähigkeitsorientierte Aufgabenzuordnung für die Mensch-Roboter-Kollaboration in sicherheitskritischen Einsatzsituationen - Gräßler, Iris; Pottebaum, Jens; Roesmann, Daniel; Mandischer, Nils; Gürtler, Marius; Hüsing, Mathias; Corves, Burkhard (Mensch und Computer 2021 - Workshopband)

Model based Integration of Human Characteristics in Production Systems: A Literature Survey - Gräßler, Iris; Roesmann, Daniel; Pottebaum, Jens (14th CIRP Conference on Intelligent Computation in Manufacturing Engineering; 15. - 17. Jul. 2020)

Generic Product Lifecycle Model: A Holistic and Adaptable Approach for Multi-Disciplinary Product-Service Systems - Gräßler, Iris; Pottebaum, Jens (Applied Sciences)

Couleur Locale - Schulze, Max (Produktive Bildstörung: Sigmar Polke und aktuelle künstlerische Positionen)
Keywords: Sigmar Polke; Bildstörung; Camouflage; Wandfarbe

Friedrich Schneider, Christus das Kind. Oratorium in drei Teilen - Werbick, Regina; Höink, Dominik; Memering, Robert

CDS Investors’ Risk Perceptions of M&A Announcements - Hippert, Benjamin; Uhde, André
Merging a sample of 492 merger and acquisition (M&A) announcements from 284 acquiring firms across Europe and North America with data from 5-year single-name credit default swaps (CDSs) written on stock-listed acquiring firms between 2005 and 2018, the paper at hand empirically analyzes the CDS investors’ risk perceptions of M&A announcements using event study methodologies. As a baseline result, we provide evidence for significantly positive cumulative average abnormal CDS spread changes for both, European and North American acquirers suggesting that CDS investors perceive an increase in the acquiring firms’ credit risk exposures due to M&A announcements. Our baseline finding holds under several robustness checks, especially when controlling for the robustness of the empirical design. Moreover, results from a large variety of sensitivity analyses reveal a number of deal and firm characteristics that may explain why CDS investors from our sample expect an increase in the acquirers’ credit risk exposures due to forthcoming M&A transactions.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study

Determinants of CDS Trading on Major Banks - Hippert, Benjamin; Uhde, André; Wengerek, Sascha Tobias
This paper empirically investigates determinants of the outstanding net notional amount of credit default swaps (CDSs) contracts written on banks. We extend and complement the previous literature dealing with CDS trading by analyzing a comprehensive set of CDS tradingspecific, bank-fundamental, macroeconomic and bank-institutional determinants. We find that risk hedging clearly dominates an investor’s speculation and arbitrage motive, while the latter, however, exhibits the strongest impact on the outstanding net notional amount of bank CDSs. Furthermore, being classified as a G-SIB, being a constituent of the main CDS index and the equity trading volume may significantly explain changes in the outstanding CDS net notional on banks. The analysis at hand provides important implications for both academics and practitioners, since understanding the trading motives of bank CDS investors provides a deeper insight into the opaque CDS market.
Keywords: banking; outstanding CDS net notional; determinants of bank CDS trading

Der Wunsch zu verschwinden - Schulze, Max
Das Buch stellt die drei jüngeren Serien Cool Mild Pure Warm (Streetfile), EPS und Der Wunsch zu verschwinden (Camopedia) des Künstlers Max Schulze vor. Ihm geht es um die Frage, an welchen Orten und auf welche Weise Malerei im Jahr 2021 entsteht: Wie sieht es mit den althergebrachten Kategorisierungen von Farbe und Form, Figuration und Abstraktion oder Fläche und Raum aus? Welche Wege sucht sich vor diesem Hintergrund die heutige Malerei und welche ästhetische Kraft ist ihr eigen? Die 32 Bilder der Serie Der Wunsch zu verschwinden (Camopedia) basieren auf den 32 Farbtönen des Systems «Alpina Feine», die Schulze verwendet, um unterschiedliche Camouflage-Muster zu malen. Dieses speziell kuratierte Farbsystem wird aus Marketinggründen mit Wohlfühlassoziationen verbunden. Diese Aufladung crasht mit der Verwendung des Tarnmusters im militärischen Bereich. Schulze beschäftigt die Frage, warum gerade heute, in einer Zeit, die von vielen politischen und sozialen Veränderungen bestimmt ist, Camouflage in Mode und Design allgegenwärtig ist. Für die Serie Cool Mild Pure Warm (Streetfile) greift Schulze ebenfalls auf Farbsysteme zurück, die er mit Fotos von diversen Farb-Attentaten im öffentlichen Raum kombiniert. So entsteht ein – nicht ganz humorloser – Kommentar zur kommerziellen Nutzung von Farbe in Farbsystemen, aber auch zu deren Zweckentfremdung durch politische «Attacken» im öffentlichen Raum. Der Name der Serie EPS bezieht sich auf ein Material, das unter dem Markennamen Styropor bekannt ist. Schulze klebt es auf abstrakte Malereien, doch nicht vollständig, sondern so, dass Teilbereiche der darunter liegenden Bildebene frei bleiben. Das darunter liegende Bild wird gleichsam verdeckt wie durch die Dämmung geschützt. Es entsteht ein ähnlich ambivalenter Seh-Eindruck wie bei den anderen Serien.
Keywords: Camouflage; Malerei; Wandfarbe; Wohlfühlstrategien; Farbsysteme; Farb-Attentat; öffentlicher Raum; Dämmung; Zwecketfremdung

Self-Trained Audio Tagging and Sound Event Detection in Domestic Environments - Ebbers, Janek; Haeb-Umbach, Reinhold (Proceedings of the 6th Detection and Classification of Acoustic Scenes and Events 2021 Workshop (DCASE2021))
In this paper we present our system for the Detection and Classification of Acoustic Scenes and Events (DCASE) 2021 Challenge Task 4: Sound Event Detection and Separation in Domestic Environments, where it scored the fourth rank. Our presented solution is an advancement of our system used in the previous edition of the task.We use a forward-backward convolutional recurrent neural network (FBCRNN) for tagging and pseudo labeling followed by tag-conditioned sound event detection (SED) models which are trained using strong pseudo labels provided by the FBCRNN. Our advancement over our earlier model is threefold. First, we introduce a strong label loss in the objective of the FBCRNN to take advantage of the strongly labeled synthetic data during training. Second, we perform multiple iterations of self-training for both the FBCRNN and tag-conditioned SED models. Third, while we used only tag-conditioned CNNs as our SED model in the previous edition we here explore sophisticated tag-conditioned SED model architectures, namely, bidirectional CRNNs and bidirectional convolutional transformer neural networks (CTNNs), and combine them. With metric and class specific tuning of median filter lengths for post-processing, our final SED model, consisting of 6 submodels (2 of each architecture), achieves on the public evaluation set poly-phonic sound event detection scores (PSDS) of 0.455 for scenario 1 and 0.684 for scenario as well as a collar-based F1-score of 0.596 outperforming the baselines and our model from the previous edition by far. Source code is publicly available at https://github.com/fgnt/pb_sed.

Adapting Sound Recognition to A New Environment Via Self-Training - Ebbers, Janek; Keyser, Moritz Curt; Haeb-Umbach, Reinhold (Proceedings of the 29th European Signal Processing Conference (EUSIPCO))
Recently, there has been a rising interest in sound recognition via Acoustic Sensor Networks to support applications such as ambient assisted living or environmental habitat monitoring. With state-of-the-art sound recognition being dominated by deep-learning-based approaches, there is a high demand for labeled training data. Despite the availability of large-scale data sets such as Google's AudioSet, acquiring training data matching a certain application environment is still often a problem. In this paper we are concerned with human activity monitoring in a domestic environment using an ASN consisting of multiple nodes each providing multichannel signals. We propose a self-training based domain adaptation approach, which only requires unlabeled data from the target environment. Here, a sound recognition system trained on AudioSet, the teacher, generates pseudo labels for data from the target environment on which a student network is trained. The student can furthermore glean information about the spatial arrangement of sensors and sound sources to further improve classification performance. It is shown that the student significantly improves recognition performance over the pre-trained teacher without relying on labeled data from the environment the system is deployed in.

Foreword to the special section on Computer Graphics education in the time of Covid - Santos, Beatriz Sousa; Domik, Gitta; Anderson, Eike Falk (Graph. Vis. Comput.)

Never ever or no matter what: Investigating Adoption Intentions and Misconceptions about the Corona-Warn-App in Germany - Häring, Maximilian; Gerlitz, Eva; Tiefenau, Christian; Smith, Matthew; Wermke, Dominik; Fahl, Sascha; Acar, Yasemin (Seventeenth Symposium on Usable Privacy and Security, SOUPS 2021, August 8-10, 2021)

On the Limited Impact of Visualizing Encryption: Perceptions of E2E Messaging Security - Stransky, Christian; Wermke, Dominik; Schrader, Johanna; Huaman, Nicolas; Acar, Yasemin; Fehlhaber, Anna Lena; Wei, Miranda; Ur, Blase; Fahl, Sascha (Seventeenth Symposium on Usable Privacy and Security, SOUPS 2021, August 8-10, 2021)

They Would do Better if They Worked Together: The Case of Interaction Problems Between Password Managers and Websites - Huaman, Nicolas; Amft, Sabrina; Oltrogge, Marten; Acar, Yasemin; Fahl, Sascha (2021 IEEE Symposium on Security and Privacy (SP))

"It’s the Company, the Government, You and I": User Perceptions of Responsibility for Smart Home Privacy and Security - Haney, Julie M.; Acar, Yasemin; Furman, Susanne (30th USENIX Security Symposium, USENIX Security 2021, August 11-13, 2021)

Investigating Web Service Account Remediation Advice - Neil, Lorenzo; Bouma-Sims, Elijah; Lafontaine, Evan; Acar, Yasemin; Reaves, Bradley (Seventeenth Symposium on Usable Privacy and Security, SOUPS 2021, August 8-10, 2021)

»Wir hören Dich nicht, schalte bitte Dein Mikro an ! « Einige Gedanken zur digitalen Lehre in der Pandemie. - Luft, Sebastian
Auch in diesem Semester finden Veranstaltungen im Fach Philosophie an den meisten Universitäten vor allem online statt; die Pandemie-Lage lässt eine Öffnung der Unis für Präsenzveranstaltungen kaum zu. Die folgenden Überlegungen hat Sebastian Luft, Professor an der Marquette University in Milwaukee/WI, aus aktuellem Anlass verfasst. 2019 erschien sein Buch »Philosophie lehren« zur philosophischen Hochschuldidaktik. Der folgende Text bietet eine aktuelle Ergänzung zur dortigen Handreichung für die philosophische Lehre.

In Amerika promovieren? Hinweise von Sebastian Luft - Luft, Sebastian (Information Philosophie)

»Hubert Fichte (…), der hamburgische Pionier der Popliteratur im langen schwingenden Pelzmantel«. Thomas Meineckes Erfindung (s)einer Tradition - Gretz, Daniela (Text + Kritik: Thomas Meinecke)

Latent Congruence Model to Investigate Similarity and Accuracy in Family Members' Perception: The Challenge of Cross-National and Cross-Informant Measurement (Non)Invariance - Tagliabue, Semira; Zambelli, Michela; Sorgente, Angela; Sommer, Sabrina; Hoellger, Christian; Buhl, Heike M.; Lanz, Margherita (Frontiers in Psychology)
Several methods are available to answer questions regarding similarity and accuracy, each of which has specific properties and limitations. This study focuses on the Latent Congruence Model (LCM; Cheung, 2009 ), because of its capacity to deal with cross-informant measurement invariance issues. Until now, no cross-national applications of LCM are present in the literature, perhaps because of the difficulty to deal with both cross-national and cross-informant measurement issues implied by those models. This study presents a step-by-step procedure to apply LCM to dyadic cross-national research designs controlling for both cross-national and cross-informant measurement invariance. An illustrative example on parent–child support exchanges in Italy and Germany is provided. Findings help to show the different possible scenarios of partial invariance, and a discussion related to how to deal with those scenarios is provided. Future perspectives in the study of parent–child similarity and accuracy in cross-national research will be discussed.
Keywords: General Psychology

Intergenerational Value Similarity and Subjective Well-Being - Hoellger, Christian; Sommer, Sabrina; Buhl, Heike M. (Journal of Family Issues)
This investigation concentrates on the association of intergenerational value similarity and adult children’s and parents’ subjective well-being, on the linkage between relationship quality and subjective well-being. Mediation effects of the relationship quality on the associations between value similarity and subjective well-being were focused. The sample consisted of 600 adult German children (53.8% women) and their parents. Dyadic correlations were constructed to determine the value similarity. In this study, the general value orientation and the family values were objects of research. We measured the subjective well-being with the Satisfaction with Life Scale and we used the Network of Relationships Inventory (NRI) to measure the relationship quality. Associations between subjective well-being and value similarity, and between subjective well-being and relationship quality, as well as mediation effects, were found. All effects depend on gender and perspective.
Keywords: Social Sciences (miscellaneous)

Digital transformation in industry - Schneider, Jennifer Nicole (Fostering Digitisation and Industry 4.0: Education – Vocation - Industry – Future. New Opportunities and Challenges for European VET. Insights in the DigI-VET Project)

Teaching and Learning Materials - Schneider, Jennifer (Fostering Digitisation and Industry 4.0: Education – Vocation - Industry – Future. New Opportunities and Challenges for European VET. Insights in the DigI-VET Project)

Förderung von Digitalisierung und Industrie 4.0: Bildung – Beruf – Industrie – Zukunft. Neue Möglichkeiten und Herausforderungen für die europäische Berufsbildung. Einblick in das Projekt DigI-VET

Differenz und Normalität in der Grundschule. Subjektive Theorien von Studierenden im Praxissemester - Cornel, Stefanie

Ethische Bildung und inklusionsorientierter Religionsunterricht - Kammeyer, Katharina (Handbuch ethische Bildung. Religionspädagogische Fokussierungen)

This is my Fight Sing - Kammeyer, Katharina (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

Der Fall Grundig(s). Europäische Krisenreaktionsstrategien auf die „Japanische Herausforderung“ im Strukturwandel - Staffel, Florian Lukas (Das Ende des „Goldenen Zeitalters“? Der Strukturwandel der 1970er Jahre, seine Rezeption und Folgen aus interdisziplinärer Perspektive)

Corona Tracing Apps – Eine Analyse und Strukturierung des europäischen Marktes - Brendel, A.B.; Greve, M.; Masuch, K.; Trang, S. (HMD Praxis der Wirtschaftsinformatik)

Examining the role of stress and information security policy design in information security compliance behaviour: An experimental study of in-task behaviour - Trang, S.; Nastjuk, I. (Computers & Security)

The perils of gamification: Does engaging with gamified services increase users’ willingness to disclose personal information? - Trang, S.; Weiger, W. (Computers in Human Behavior)

Explanation as a Social Practice: Toward a Conceptual Framework for the Social Design of AI Systems - Rohlfing, Katharina J.; Cimiano, Philipp; Scharlau, Ingrid; Matzner, Tobias; Buhl, Heike M.; Buschmeier, Hendrik; Esposito, Elena; Grimminger, Angela; Hammer, Barbara; Haeb-Umbach, Reinhold; Horwath, Ilona; Hüllermeier, Eyke; et al. (IEEE Transactions on Cognitive and Developmental Systems)
One objective of current research in explainable intelligent systems is to implement social aspects in order to increase the relevance of explanations. In this paper, we argue that a novel conceptual framework is needed to overcome shortcomings of existing AI systems with little attention to processes of interaction and learning. Drawing from research in interaction and development, we first outline the novel conceptual framework that pushes the design of AI systems toward true interactivity with an emphasis on the role of the partner and social relevance. We propose that AI systems will be able to provide a meaningful and relevant explanation only if the process of explaining is extended to active contribution of both partners that brings about dynamics that is modulated by different levels of analysis. Accordingly, our conceptual framework comprises monitoring and scaffolding as key concepts and claims that the process of explaining is not only modulated by the interaction between explainee and explainer but is embedded into a larger social context in which conventionalized and routinized behaviors are established. We discuss our conceptual framework in relation to the established objectives of transparency and autonomy that are raised for the design of explainable AI systems currently.
Keywords: Explainability; process ofexplaining andunderstanding; explainable artificial systems

Chapter 5: Quantitative methodological approaches to citizenship and migration - Malancu, Natalia; Florea, Alexandra (Handbook of Citizenship and Migration)

Ausblick auf die COP26 in Glasgow, Eine schrittweise Erhöhung der Klimaschutzbeiträge reicht nicht – ein Klimaklub sollte mitgedacht werden - Alt, Marius; Gallier, Carlo; Sturm, Bodo; Kesternich, Martin

Transparente Klimabilanzen - Information für klimafreundliches Handeln - Frick, Marc; Conzelmann, Annabell; von Graevenitz, Kathrine; Kesternich, Martin; Wagner, Ulrich; Rausch, Sebastian

Barth for Future? Eine Barth-Relektüre vor dem Hintergrund der Bewegung „Fridays for Future“. - Meyer zu Hörste-Bührer, Raphaela (Römerbrief und Tageszeitung! Politik in der Theologie Karl Barths.)

Breeding Diverse Packings for the Knapsack Problem by Means of Diversity-Tailored Evolutionary Algorithms - Bossek, Jakob; Neumann, Aneta; Neumann, Frank (Proceedings of the Genetic and Evolutionary Computation Conference)
In practise, it is often desirable to provide the decision-maker with a rich set of diverse solutions of decent quality instead of just a single solution. In this paper we study evolutionary diversity optimization for the knapsack problem (KP). Our goal is to evolve a population of solutions that all have a profit of at least (1 - {$ϵ$}) {$·$} OPT, where OPT is the value of an optimal solution. Furthermore, they should differ in structure with respect to an entropy-based diversity measure. To this end we propose a simple ({$μ$} + 1)-EA with initial approximate solutions calculated by a well-known FPTAS for the KP. We investigate the effect of different standard mutation operators and introduce biased mutation and crossover which puts strong probability on flipping bits of low and/or high frequency within the population. An experimental study on different instances and settings shows that the proposed mutation operators in most cases perform slightly inferior in the long term, but show strong benefits if the number of function evaluations is severely limited.
Keywords: evolutionary algorithms; evolutionary diversity optimization; knapsack problem; tailored operators

Exact Counting and~Sampling of Optima for the Knapsack Problem - Bossek, Jakob; Neumann, Aneta; Neumann, Frank (Learning and Intelligent Optimization)
Computing sets of high quality solutions has gained increasing interest in recent years. In this paper, we investigate how to obtain sets of optimal solutions for the classical knapsack problem. We present an algorithm to count exactly the number of optima to a zero-one knapsack problem instance. In addition, we show how to efficiently sample uniformly at random from the set of all global optima. In our experimental study, we investigate how the number of optima develops for classical random benchmark instances dependent on their generator parameters. We find that the number of global optima can increase exponentially for practically relevant classes of instances with correlated weights and profits which poses a justification for the considered exact counting problem.
Keywords: Dynamic programming; Exact counting; Sampling; Zero-one knapsack problem

Evolutionary Diversity Optimization and the Minimum Spanning Tree Problem - Bossek, Jakob; Neumann, Frank (Proceedings of the Genetic and Evolutionary Computation Conference)
In the area of evolutionary computation the calculation of diverse sets of high-quality solutions to a given optimization problem has gained momentum in recent years under the term evolutionary diversity optimization. Theoretical insights into the working principles of baseline evolutionary algorithms for diversity optimization are still rare. In this paper we study the well-known Minimum Spanning Tree problem (MST) in the context of diversity optimization where population diversity is measured by the sum of pairwise edge overlaps. Theoretical results provide insights into the fitness landscape of the MST diversity optimization problem pointing out that even for a population of {$μ$} = 2 fitness plateaus (of constant length) can be reached, but nevertheless diverse sets can be calculated in polynomial time. We supplement our theoretical results with a series of experiments for the unconstrained and constraint case where all solutions need to fulfill a minimal quality threshold. Our results show that a simple ({$μ$} + 1)-EA can effectively compute a diversified population of spanning trees of high quality.
Keywords: evolutionary algorithms; evolutionary diversity optimization; minimum spanning tree; runtime analysis

Do Additional Optima Speed up Evolutionary Algorithms? - Bossek, Jakob; Sudholt, Dirk (Proceedings of the 16th ACM/SIGEVO Conference on Foundations of Genetic Algorithms)
Most runtime analyses of randomised search heuristics focus on the expected number of function evaluations to find a unique global optimum. We ask a fundamental question: if additional search points are declared optimal, or declared as desirable target points, do these additional optima speed up evolutionary algorithms? More formally, we analyse the expected hitting time of a target set OPT {$\cup$} S where S is a set of non-optimal search points and OPT is the set of optima and compare it to the expected hitting time of OPT. We show that the answer to our question depends on the number and placement of search points in S. For all black-box algorithms and all fitness functions we show that, if additional optima are placed randomly, even an exponential number of optima has a negligible effect on the expected optimisation time. Considering Hamming balls around all global optima gives an easier target for some algorithms and functions and can shift the phase transition with respect to offspring population sizes in the (1,{$λ$}) EA on One-Max. Finally, on functions where search trajectories typically join in a single search point, turning one search point into an optimum drastically reduces the expected optimisation time.
Keywords: evolutionary algorithms; pseudo-boolean functions; runtime analysis; theory

On the Potential of Normalized TSP Features for Automated Algorithm Selection - Heins, Jonathan; Bossek, Jakob; Pohl, Janina; Seiler, Moritz; Trautmann, Heike; Kerschke, Pascal (Proceedings of the 16th ACM/SIGEVO Conference on Foundations of Genetic Algorithms)
Classic automated algorithm selection (AS) for (combinatorial) optimization problems heavily relies on so-called instance features, i.e., numerical characteristics of the problem at hand ideally extracted with computationally low-demanding routines. For the traveling salesperson problem (TSP) a plethora of features have been suggested. Most of these features are, if at all, only normalized imprecisely raising the issue of feature values being strongly affected by the instance size. Such artifacts may have detrimental effects on algorithm selection models. We propose a normalization for two feature groups which stood out in multiple AS studies on the TSP: (a) features based on a minimum spanning tree (MST) and (b) a k-nearest neighbor graph (NNG) transformation of the input instance. To this end we theoretically derive minimum and maximum values for properties of MSTs and k-NNGs of Euclidean graphs. We analyze the differences in feature space between normalized versions of these features and their unnormalized counterparts. Our empirical investigations on various TSP benchmark sets point out that the feature scaling succeeds in eliminating the effect of the instance size. Eventually, a proof-of-concept AS-study shows promising results: models trained with normalized features tend to outperform those trained with the respective vanilla features.
Keywords: automated algorithm selection; graph theory; instance features; normalization; traveling salesperson problem (TSP)

Generating Instances with Performance Differences for More than Just Two Algorithms - Bossek, Jakob; Wagner, Markus (Proceedings of the Genetic and Evolutionary Computation Conference Companion)
In recent years, Evolutionary Algorithms (EAs) have frequently been adopted to evolve instances for optimization problems that pose difficulties for one algorithm while being rather easy for a competitor and vice versa. Typically, this is achieved by either minimizing or maximizing the performance difference or ratio which serves as the fitness function. Repeating this process is useful to gain insights into strengths/weaknesses of certain algorithms or to build a set of instances with strong performance differences as a foundation for automatic per-instance algorithm selection or configuration. We contribute to this branch of research by proposing fitness-functions to evolve instances that show large performance differences for more than just two algorithms simultaneously. As a proof-of-principle, we evolve instances of the multi-component Traveling Thief Problem (TTP) for three incomplete TTP-solvers. Our results point out that our strategies are promising, but unsurprisingly their success strongly relies on the algorithms’ performance complementarity.
Keywords: evolutionary algorithms; evolving instances; fitness function; instance hardness; traveling thief problem (TTP)

Entropy-Based Evolutionary Diversity Optimisation for the Traveling Salesperson Problem - Nikfarjam, Adel; Bossek, Jakob; Neumann, Aneta; Neumann, Frank (Proceedings of the Genetic and Evolutionary Computation Conference)
Computing diverse sets of high-quality solutions has gained increasing attention among the evolutionary computation community in recent years. It allows practitioners to choose from a set of high-quality alternatives. In this paper, we employ a population diversity measure, called the high-order entropy measure, in an evolutionary algorithm to compute a diverse set of high-quality solutions for the Traveling Salesperson Problem. In contrast to previous studies, our approach allows diversifying segments of tours containing several edges based on the entropy measure. We examine the resulting evolutionary diversity optimisation approach precisely in terms of the final set of solutions and theoretical properties. Experimental results show significant improvements compared to a recently proposed edge-based diversity optimisation approach when working with a large population of solutions or long segments.
Keywords: evolutionary algorithms; evolutionary diversity optimisation; high-order entropy; traveling salesperson problem

Diversifying Greedy Sampling and Evolutionary Diversity Optimisation for Constrained Monotone Submodular Functions - Neumann, Aneta; Bossek, Jakob; Neumann, Frank (Proceedings of the Genetic and Evolutionary Computation Conference)
Submodular functions allow to model many real-world optimisation problems. This paper introduces approaches for computing diverse sets of high quality solutions for submodular optimisation problems with uniform and knapsack constraints. We first present diversifying greedy sampling approaches and analyse them with respect to the diversity measured by entropy and the approximation quality of the obtained solutions. Afterwards, we introduce an evolutionary diversity optimisation (EDO) approach to further improve diversity of the set of solutions. We carry out experimental investigations on popular submodular benchmark problems and analyse trade-offs in terms of solution quality and diversity of the resulting solution sets.
Keywords: evolutionary algorithms; evolutionary diversity optimisation; sub-modular functions

Computing Diverse Sets of High Quality TSP Tours by EAX-based Evolutionary Diversity Optimisation - Nikfarjam, Adel; Bossek, Jakob; Neumann, Aneta; Neumann, Frank (Proceedings of the 16th ACM}/SIGEVO Conference on Foundations of Genetic Algorithms)
Evolutionary algorithms based on edge assembly crossover (EAX) constitute some of the best performing incomplete solvers for the well-known traveling salesperson problem (TSP). Often, it is desirable to compute not just a single solution for a given problem, but a diverse set of high quality solutions from which a decision maker can choose one for implementation. Currently, there are only a few approaches for computing a diverse solution set for the TSP. Furthermore, almost all of them assume that the optimal solution is known. In this paper, we introduce evolutionary diversity optimisation (EDO) approaches for the TSP that find a diverse set of tours when the optimal tour is known or unknown. We show how to adopt EAX to not only find a high-quality solution but also to maximise the diversity of the population. The resulting EAX-based EDO approach, termed EAX-EDO is capable of obtaining diverse high-quality tours when the optimal solution for the TSP is known or unknown. A comparison to existing approaches shows that they are clearly outperformed by EAX-EDO.
Keywords: edge assembly crossover (EAX); evolutionary algorithms; evolutionary diversity optimisation (EDO); traveling salesperson problem (TSP)

Time Complexity Analysis of Randomized Search Heuristics for the Dynamic Graph Coloring Problem - Bossek, Jakob; Neumann, Frank; Peng, Pan; Sudholt, Dirk (Algorithmica)
We contribute to the theoretical understanding of randomized search heuristics for dynamic problems. We consider the classical vertex coloring problem on graphs and investigate the dynamic setting where edges are added to the current graph. We then analyze the expected time for randomized search heuristics to recompute high quality solutions. The (1+1) Evolutionary Algorithm and RLS operate in a setting where the number of colors is bounded and we are minimizing the number of conflicts. Iterated local search algorithms use an unbounded color palette and aim to use the smallest colors and, consequently, the smallest number of colors. We identify classes of bipartite graphs where reoptimization is as hard as or even harder than optimization from scratch, i.e., starting with a random initialization. Even adding a single edge can lead to hard symmetry problems. However, graph classes that are hard for one algorithm turn out to be easy for others. In most cases our bounds show that reoptimization is faster than optimizing from scratch. We further show that tailoring mutation operators to parts of the graph where changes have occurred can significantly reduce the expected reoptimization time. In most settings the expected reoptimization time for such tailored algorithms is linear in the number of added edges. However, tailored algorithms cannot prevent exponential times in settings where the original algorithm is inefficient.
Keywords: Dynamic optimization; Evolutionary algorithms; Running time analysis

Rezension zu: Dräger, Marco: Denkmäler im Geschichtsunterricht Frankfurt am Main 2021. - Fastlabend-Vargas, Daniel (H-Soz-Kult)

Model approaches for closed-loop property control for flow forming - Riepold, Markus; Arian, Bahman; Vasquez, Julian Rozo; Homberg, Werner; Walther, Frank; Trächtler, Ansgar (Advances in Industrial and Manufacturing Engineering)
The implementation of control systems in metal forming processes improves product quality and productivity. By controlling workpiece properties during the process, beneficial effects caused by forming can be exploited and integrated in the product design. The overall goal of this investigation is to produce tailored tubular parts with a defined locally graded microstructure by means of reverse flow forming. For this purpose, the proposed system aims to control both the desired geometry of the workpiece and additionally the formation of strain-induced α′-martensite content in the metastable austenitic stainless steel AISI 304 L. The paper introduces an overall control scheme, a geometry model for describing the process and changes in the dimensions of the workpiece, as well as a material model for the process-induced formation of martensite, providing equations based on empirical data. Moreover, measurement systems providing a closed feedback loop are presented, including a novel softsensor for in-situ measurements of the martensite content.

"Searching for a Belgian culinary identity - Referat von Prof. Dr. Peter Scholliers" (VIDEO) - Huybrechts, Yves; Scholliers, Peter

"Der belgische Symbolismus - Interview mit dem Direktor der Alten Nationalgalerie, Dr. Ralph Gleis" (PODCAST) - Huybrechts, Yves

"Gebaute Träume - Wohnkultur in Flandern und Wallonien" (VIDEO) - Huybrechts, Yves